COMPARISON BETWEEN LAPARATOMY AND LAPARASCOPY COLORECTAL CANCER FOR LENGTH OF HOSPITAL, SURGICAL SITE INFECTION AND INTRAPERITONEUM ADHESION - Ahmad Wasil; Saekhol Bakri; Yan Wisnu; Abdul Mughni (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Colorectal cancer (CRC) is the development of cancer from the colon or rectum. There are two kinds of surgery which are laparotomy and laparoscopy. This course of action had a significant effect on the length of stay, surgical site infection, and intraperitoneal adhesion. The purpose of this study is to find out the comparison between laparotomy and colorectal cancer laparoscopy with the length of stay, surgical site infection and intraperitoneal adhesion. The researcher used a cross sectional design. The sample for this study was taken from the medical record data of colorectal cancer patients in Dr. Kariadi Semarang from 2013 to 2018. The data were collected using purposive sampling technique. There were 57 samples that included inclusion and exclusion criteria with 28 details of laparoscopy and 29 samples of laparotomy. Numeric-scale data were tested for normality of data by Kolmogorov-Smirnov and found abnormal data using the Mann Whitney test. Nominal scale data were processed using the non-parametric Chi-Square test and it significant if p<0.05. There is a difference in length of stay and frequency of occurrence of surgical site infections and intraperitoneal adhesion between laparotomy and laparoscopy.